Maize flour price trends in rural districts and urban districts of Lesotho under COVID-19 - Nhlengethwa, Sibusiso; Matchaya, Greenwell C.; Greffiths, Ikhothatseng Jacob; Fakudze, Bhekiwe (2020)
This bulletin focuses on the relationship between maize flour price trends and the actions in response to COVID-19 Pandemic in Lesotho. An understanding of food price movement is important for providing guidance on policy interventions that would ensure food security among households and the country at large.